Astigmatic change after pterygium excision with autologous limbal conjunctival graft - Sharma, Dikchhya; Prasai, Gunjan; Malla, Om Krishna (Journal of Kathmandu Medical College, 2020)
Background: Pterygium induces a significant amount of astigmatism. Pterygium excision with conjunctival limbal autograft results in significant reduction in astigmatism by inducing a reversal of pterygium induced corneal flattening thereby improving the vision. Objectives: The aim of this study was to investigate the amount of corneal astigmatism in patients with pterygium before and one month (4 weeks) after surgery. Methodology: The prospective observational study was conducted in 31 patients who underwent pterygium excision with limbal autograft in Kathmandu Medical College Teaching Hospital during the study period of 12 months duration. Patients with recurrent pterygium, pseudopterygium, history of ocular trauma, history of ocular surgery, corneal scarring were excluded from the study. After surgery, patients were followed for four weeks. Findings were recorded in the proforma and statistical analysis was done in SPSS version 19. Results: Pterygium was seen in all age groups with majority being in the active age range of 41-50 yrs. Females were most commonly affected. Significant difference in corneal astigmatism was noted postoperatively with a p value being 0.01. Conclusion: The technique of pterygium excision with limbal conjunctival autograft not only reduces the chances of recurrence but also helps in reducing the induced corneal astigmatism which is responsible for decreased vision in patients with pterygium.